‘Thus you will say to them’: A Cross-Cultural Confessional Polemic in Jeremiah 10.11 - Reid, Garnett (Journal for the study of the Old Testament, 2006)
The unexpected presence of Aramaic in Jer. 10.11 has prompted some scholars to conclude: (1) that the verse is an intrusive insertion into the 10.1-16 unit; and (2) that the entire poem lacks cohesion and is ill-fitting in its context. This study contends that, in response to the latter charge, rhetorical order is evident in the structure of 10.1-16. Furthermore, the claim that v. 11 is out of place fails to consider both its pivotal position and kerygmatic intent within the pre-captivity Jeremianic setting. Shared themes link the larger poem with its context, while clearly delineated rhetorical devices demonstrate its structural cohesion. Verse 11 serves as the architectural axis of the unit. Its Aramaic rendering is crucial given its intended use as a polemical summary of the Hebrews’ theology, designed as a kerygmatic challenge they are to deliver to their Babylonian captors proclaiming Yahweh as the true God.